Pengaruh Jenis Mordan dalam Pembuatan Eco Print pada Hasil Jadi Scarf - Refina Irbah; Ma’rifatun Nasikhah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to analyze the effect of different mordant types on the quality of ecoprinted scarves, particularly in terms of color sharpness and motif clarity. A controlled experimental method was conducted by testing three types of mordants—alum, sodium acetate, and iron sulfate—on cotton fabric using the pounding technique. Each treatment was evaluated by 30 respondents to ensure statistical validity. The results revealed significant differences (p<0.05) among the three mordants, with alum demonstrating the best performance, achieving a color sharpness score of 3.8 and motif clarity of 3.7, followed by iron sulfate (3.2 for color and 3.1 for motif), while sodium acetate yielded the lowest scores (2.6 for color and 2.9 for motif). The superiority of alum is attributed to the optimal fixation capability of Al³⁺ ions and pH stability within the range of 5.2–5.8. The research instruments were validated (r=0.92) and reliable (α=0.89). These findings provide significant contributions to the advancement of ecoprinting techniques, particularly in mordant selection for producing high-quality textile products.